The Influence of Techno stress and Organizational-Is Related Support on User Satisfaction in Government Organizations: A Proposed Model and Literature Review - Ibrahim, Hadziroh; ., Nur Zahiyah Othman (Information Management and Business Review, 2014)
Empirical evidence on the issue of satisfaction towards certain computer applications or systems has guided organizations in the implementation process of information systems (IS). What is more important, findings of the previous studies in the IS field have proved that user satisfaction is one dimension of IS success and needs to be carefully managed during the implementation process. Consequently, organizations are increasingly concerned about ensuring that employees have gained satisfaction about the IS that they use. Organizations also need to investigate user opinions about the system, and where its faults lie. Though there are a great number of studies on IS, little attention has been given to the influence of technostress and organizational IS-related support on IS success in government organizations of Malaysia. Two hypotheses were generated from the previous studies which link technostress, organizational IS-related support with user satisfaction. These hypotheses will be tested in the future. The results from the research would contribute useful insights in EHRM studies. Particularly, the results would help the government organizations in Malaysia to improve their implementation of HRMIS.